2020
DOI: 10.1002/adom.202000645
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Beam Manipulation at Telecommunication Wavelengths Enabled by an All‐Dielectric Metasurface Doublet

Abstract: Multifunctional metasurfaces, which are planar devices featuring diverse functionalities, have attracted tremendous attention as they enable highly dense integration and miniaturization of photonic devices. Previous approaches based on spatial/spectral multiplexing of meta‐atoms on single metasurfaces are supposed to be inevitably limited in their functional diversity. An additional degree of freedom for design, achieved by cascading multiple metasurfaces into a single metasystem, promotes new combinations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 79 publications
1
1
0
Order By: Relevance
“…These spiral fringe patterns may be attributed to the interference between the divergent optical vortex and the incident beam with a large footprint . In light of the issue of low modulation efficiency as in the cases of metasurface devices, the unmodulated beam may perturb the vortex beam, which will result in a spiral-fringe-shaped vortex beam. , By counting the interference fringes, we confirmed that the generated vortex beam assumed an optical angular momentum l = 5. To explore the polarization dependence of the metasurface, the intensity profiles of the vortex beams were verified for normal incidence.…”
Section: Resultssupporting
confidence: 52%
“…These spiral fringe patterns may be attributed to the interference between the divergent optical vortex and the incident beam with a large footprint . In light of the issue of low modulation efficiency as in the cases of metasurface devices, the unmodulated beam may perturb the vortex beam, which will result in a spiral-fringe-shaped vortex beam. , By counting the interference fringes, we confirmed that the generated vortex beam assumed an optical angular momentum l = 5. To explore the polarization dependence of the metasurface, the intensity profiles of the vortex beams were verified for normal incidence.…”
Section: Resultssupporting
confidence: 52%
“…SiN also suffers from less nonlinear losses with respect to Si [61], which allows waveguide Another method is to enlarge the FOV of PIC-OPA assisted by metasurfaces (named meta-assisted PIC-OPA). As shown in Figure 6b, the metasurface performs like an ultra-thin lens, which can enlarge the beam steering angle θ by M times [47][48][49]. Lee et al proposed and demonstrated a bidirectional grating antenna PIC-OPA integrated with a miniaturized all-dielectric metasurface doublet formed on a glass substrate atop the antenna array.…”
Section: Pic-opamentioning
confidence: 99%